Fabrication of a tissue engineered scaffold-free cartilage graft for temporomandibular condylar repair with living hyaline cartilaginous graft in rabbit models - Soh, Wei Yan (2018)
Articular cartilage tissue is effective for joint movements to be smooth and frictionless, however it has low self-recovery ability because of its avascular nature. Osteoarthritis (OA) is a disease causing joint pain, joint deformity, and functional disability. Temporomandibular joint (TMJ) links the lower jaw, mandible, and temporal bone which is in front of the ear. Temporomandibular joint disorder may develop due to trauma or OA can cause a long term pain and restriction to the jaw movement, which affects the quality of life. Although studies were done on articular cartilage defects experimentally, no consistent clinical protocol has been confirmed yet. The developing cartilage tissue engineering strategies to regenerate condylar cartilage have gathered a lot of attention and are seen to be the new promising therapeutic approaches. This project aims to develop a tissue engineered ‘scaffold-free’ graft to repair the TMJ condylar cartilage using rabbit models. The use of ‘living hyaline cartilage graft’ (LhCG), a xenogenic synthetic scaffold free construct with hyaline quality, will be demonstrated for treating cartilage lesions in 28 rabbit models in 4 different groups. The assessment will be on macroscopic and microscopic inspection on the restoration of cartilage thickness, promotion of incorporation with neighboring native cartilage, cartilage-specific matrix molecules, and establishing an intact superficial tangential zone again. The outcome of this pioneering work would repair damaged TMJ cartilage using tissue engineering approach and is especially relevant in our ageing population where rising number of joint degenerative disorders are expected.